Estilos de pensamiento en estudiantes de estudios generales de una universidad de Lima Metropolitana - Robles Mori, Herbert (2006)
A total of 525 students of a University of Lima, was put under a descriptive study. The instrument was the Test of styles of Thought, created, by the United of Investigation of the Faculty of Psychology of the Feminine University of the Sacred Heart. According to the results it is possible to be observed that the Styles Judicial, Conserved and Liberal are those that stand out by by a greater percentage of normality, also determine relation between the age with Legislative, Judicial, Hierarchic, Monarchic, Global, Local and Executive style.